Análise ergonômica do setor de corte em uma confecção de camisaria situada no interior da zona da mata mineira - Carneiro, Priscila França Gonzaga (2018)
This work analyzes the ergonomic conditions in the sector of cut of a women's dressing room located in the Zona da Mata Mineira, that is, it has the objective of analyzing the regions of the body to which the workers of this sector feel more pains and that have caused estrangement. Initially, an adapted questionnaire was used to analyze data on the profile, working conditions and health of workers. In addition, Corllet's body map, Couto's check list and NR 17 were used to identify and analyze the ergonomic hazards to which employees are involved such as positions required for the activities and adequacy of the furniture. The work environment proved to be conducive to the development of occupational diseases such as RSI / DORT, since there are items that are not in conformity with the NR-17, such as the need for seating for rest and irregular height of the table where the cutting is performed of the fabric. The regions of the body with more pain complaints were the cervical region, upper back and legs (right and left), since they are the regions most affected in the exercise of the function. It is suggested changes in the working environment regarding furniture, the practice of physical exercises, physical therapy, in addition to breaks for rest or work.